Rotary drum soil blending for source zone remediation: Various application scenarios. Issue 3 (6th June 2018) - Markesic, Steve; Rossabi, Joe; Haselow, John; Romano, Jay; Adams, Tim
Abstract: Mechanical blending of contaminated soil with amendments has recently reemerged as an important treatment technology. From its original application using large‐diameter augers in the early 1990s to the current use of rotary drum blenders, soil blending is being used as an alternative to other remediation technologies like amendment injection and soil vapor and groundwater extraction. Shallow (approximately 10 m below ground surface [bgs] or less) soil blending also offers an alternative to excavation and disposal. Soil blending has been used to remediate a site with various contaminants including, but not limited to, chlorinated solvents, petroleum, and metals. The types of soils susceptible to soil blending vary from sands and gravels to silts and clays to fractured rock and combinations of all of these. The types of amendments blended include oxidants, reducing agents, biological enhancements, and stabilizing amendments. Soil blending systems deliver the power to the mixing head to adequately mix the soil and amendment to enhance remediation effectiveness. Since long‐term contamination is often a result of heterogeneously distributed residual contaminant in localized source zones that are difficult to access, the typical aim of soil blending is to homogenize the soil while effectively distributing amendment to these zones made accessible by blending. By effectively homogenizing the soil, however, soil blending will increase the void ratio and disrupt the shear strength and bearing capacity of the soil so an important component of a soil blending technology is proper recovery of these geotechnical parameters. This can be achieved by using well‐known soil improvement techniques such as amending all or a portion of the blended area with Portland cement or lime. Several case studies of soil blending treatments of different contaminants and amendments in various soil types are provided.